The Role of Social Humanities in Protecting Young People from Moral Threats in the Context of Globalization - Adham qizi, Ulasheva Sabina (Journal of Innovation in Education and Social Research, 2024)
In this article, it is described that at the stage of today's information society, it is very important to educate young people, to protect them from information attacks and spiritual threats, and to organize spiritual and educational promotion activities based on the requirements of the time. Therefore, in the education system, the main focus is on protecting our children from various ideological attacks and threats such as "mass culture", and on forming a conscious and active attitude to life and a sense of belonging in each of our young generations. people. Especially at the stage of today's information society, it is our responsibility to protect our children from threats such as various religious extremist, terrorist foreign ideas, and "mass culture".